2023
DOI: 10.1097/ms9.0000000000001244
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, and economy of shensongyangxin capsules for the treatment of coronary heart disease arrhythmia: a meta-analysis of randomized controlled trials

Luyao Ma,
Libing Li,
Fujin Ma
et al.

Abstract: Background: Shensong Yangxin Capsules (SSYX) is a proprietary Chinese medicine commonly, used in the treatment of arrhythmia. In recent years, a flurry of randomized controlled trials of SSYX was reported in the treatment of Coronary heart disease arrhythmia in China. However, these experiments have not been systematically evaluated by economics. The purpose of this study was to assess the efficacy, safety, and economy of the SSYX in the treatment of arrhythmia in patients with coronary heart disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…These lines of evidence suggest that NGR1 may improve DCM through TGF-β/Smad2/3 and AKT/Nrf2 signaling pathways. Shensong Yangxin capsule (SSYX) is a TCM prescription widely used to treat arrhythmia and has been used clinically for many years ( Cao et al, 2021 ; Ma et al, 2023 ). Shen et al (2014) found that SSYX significantly reduced the heart weight/body weight ratio of fat emulsion + STZ-induced diabetic rats and improved the degree of cardiac dysfunction, myocardial fibrosis, and collagen deposition.…”
Section: Signaling Pathways In Tcm Intervening the Pathological Progr...mentioning
confidence: 99%
“…These lines of evidence suggest that NGR1 may improve DCM through TGF-β/Smad2/3 and AKT/Nrf2 signaling pathways. Shensong Yangxin capsule (SSYX) is a TCM prescription widely used to treat arrhythmia and has been used clinically for many years ( Cao et al, 2021 ; Ma et al, 2023 ). Shen et al (2014) found that SSYX significantly reduced the heart weight/body weight ratio of fat emulsion + STZ-induced diabetic rats and improved the degree of cardiac dysfunction, myocardial fibrosis, and collagen deposition.…”
Section: Signaling Pathways In Tcm Intervening the Pathological Progr...mentioning
confidence: 99%